A novel liquid optical filter based on magnetic electrolyte nanofluids for hybrid photovoltaic/thermal solar collector application. (October 2017) - Jin, Jingyu; Jing, Dengwei
Graphical abstract: In the present study, we proposed, for the first time, a novel magnetic electrolyte nanofluid (ENF) as liquid optical filters for hybrid photovoltaic/thermal (PV/T) application. The obtained two stable ENF filters satisfactorily match the optical absorption of two typical PV cells, Si and InGaP, respectively. Highlights: A novel ENF based liquid optical filter for PV/T application is proposed. ENF filters satisfactorily match the absorbance of Si and InGaP, respectively. Particle size and thermal conductivity of the optimized filters are investigated. The applicability of our ENF filters is testified based on a 2D PV/T model. Abstract: Different from solid optical filters, the nanofluid filters display various optical properties and can also be easily pumped at low cost. However, finding a proper nanofluid meeting the standard of practical application is a great challenge. In the present study, we propose a novel magnetic electrolyte nanofluid (ENF) for the first time which can be potentially used as liquid optical filters for hybrid photovoltaic/thermal (PV/T) application. By dispersing optimized amount of magnetic iron oxide (Fe3 O4 ) nanoparticles in 50% water/50% EG solutions containing methylene blue (MB) or copper sulfate (CS), we obtained two stable ENF filters satisfactorily meeting the optical absorption of two typical PV cells, Si and InGaP, respectively. Due to its magnetism, ENF can be considered as a smart liquid optical filter controllable by external magnetic field. The root-mean-square errors (RMSE) of the absorptance between the ENF filters and the corresponding ideal filters are both smaller than that of water-based nanofluid filters containing typical core/shell nanoparticles while their thickness is much smaller. The stability, particle size distribution and thermal conductivity of the optimized ENF filters were investigated. It was found that both ENF filters have good stability and higher thermal conductivities than their base fluids. Performance of ENF filters in PV/T system was evaluated based on a reported theoretical model. The results showed that the values of merit function (MF) for the two types of ENF based PV/T systems are both higher than that of typical core/shell nanoparticle nanofluid filters. Overall, our study demonstrates that ENF represents an efficient, low-cost and smart liquid optical filter for the application in PV/T system.